Relevansi Aplikasi Peer To Peer (P2P) Lending Student Loan pada Mahasiswa dalam Lingkup Hukum Islam - Muhammad Al berto, (Sunan Kalijaga: Islamic Economics Journal, 2024)
Advances in financial services technology in the form of Peer to Peer (P2P) Lending have had an impact on facilitating the public in financing activities and have penetrated all sectors, one of which is the education financing sector in tertiary institutions in the form of Student Loans. This study aims to analyze the contracts contained in P2P Lending Student Loans. This study uses qualitative methods by reviewing previous literature. The results of this study are that the credit agreement on P2P Lending Student Loans has a Qardh contract in it. However, in the Qardh contract, there are conditions for the addition of both additional loan principal and late fees that are given if the borrower cannot repay the loan in accordance with the agreement which is prohibited by Islamic law.